Nest-site competition between invasive and native cavity nesting birds and its implication for conservation. (1st October 2016) - Charter, Motti; Izhaki, Ido; Ben Mocha, Yitzchak; Kark, Salit
Abstract: Nesting cavities are often a limited resource that multiple species use. There is an ongoing discussion on whether invasive cavity nesting birds restrict the availability of this key limited resource. While the answer to this question has important conservation implications, little experimental work has been done to examine it. Here, we aimed to experimentally test whether alien cavity nesting birds affect the occupancy of cavities and the resulting breeding success of native cavity breeders in a large urban park located in Tel Aviv, Israel. Over three breeding seasons, we manipulated the entry size of nest boxes and compared the occupancy and breeding success of birds in nest boxes of two treatments. These included nest boxes with large-entrance and small-entrance holes. The large-entrance holes allowed access for both the native and invasive birds (the two main aliens in the park are the common mynas and rose-ringed parakeets). The smaller-entrance boxes, on the other hand, allowed only the smaller sized native cavity breeders (great tits and house sparrows) to enter the boxes but prevented the alien species from entering. We found that the large-entrance nest boxes were occupied by five different bird species, comprising three natives (great tit, house sparrow, Scops owl) and two invasive species (common myna, rose-ringed parakeet) while the small-entrance boxes were only occupied by the two native species. The alien common mynas and rose-ringed parakeets occupied 77.5% of the large-entrance nest boxes whereas native species, mainly great tits, occupied less than 9% of the large-entrance boxes and 36.5% of the small-entrance boxes. When examining the occupancy of those cavities that were not occupied by the aliens, natives occupied both the small and large-entrance nest boxes equally. Three quarters (78%) of the great tits breeding in the large-entrance boxes were usurped by common mynas during the breeding season and as a result breeding success was significantly lower for great tits breeding in the large-entrance boxes compared with the small-entrance boxes. The results of this study suggests that the invasive alien species can reduce the breeding potential of native cavity breeders both by exploiting the limited breeding resource (nest cavities) and by directly usurping cavities already occupied by the native species. Since the majority of large-entrance nest boxes were occupied by the larger alien birds, less native species bred in the limited number of unoccupied large-entrance nest boxes because of exploitation competition. We propose that for management purposes, nest-box programs that alter the entrance size of available natural cavities may be a practical approach, reducing the competition between native cavity breeders and alien invasive birds, and especially benefiting the smaller native cavity breeders. Highlights: Alien species occupied most nest boxes leaving limited numbers to native species. Breeding success of native tits was lower in nests than aliens could enter. Alien myna usurped most native great tit nests. Adding nest boxes eliminates nest site competition with alien species.